2010
DOI: 10.1007/s10585-010-9359-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hybrid cells derived from spontaneous fusion events between breast epithelial cells exhibiting stem-like characteristics and breast cancer cells

Abstract: Several data of the past years clearly indicated that the fusion of tumor cells and tumor cells or tumor cells and normal cells can give rise to hybrids cells exhibited novel properties such as an increased malignancy, drug resistance, or resistance to apoptosis. In the present study we characterized hybrid cells derived from spontaneous fusion events between the breast epithelial cell line M13SV1-EGFP-Neo and two breast cancer cell lines: HS578T-Hyg and MDA-MB-435-Hyg. Short-tandemrepeat analysis revealed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
93
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(113 citation statements)
references
References 49 publications
12
93
0
Order By: Relevance
“…Both hybrid clones derived from spontaneous fusion events between M13SV1-EGFP-Neo cells and MDA-MB-435-Hyg cells and were isolated by a dual antibiotic selection procedure [7]. Parental cells were co-cultured for 24 h prior to addition of antibiotics [7].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both hybrid clones derived from spontaneous fusion events between M13SV1-EGFP-Neo cells and MDA-MB-435-Hyg cells and were isolated by a dual antibiotic selection procedure [7]. Parental cells were co-cultured for 24 h prior to addition of antibiotics [7].…”
Section: Resultsmentioning
confidence: 99%
“…Both hybrid clones derived from spontaneous fusion events between M13SV1-EGFP-Neo cells and MDA-MB-435-Hyg cells and were isolated by a dual antibiotic selection procedure [7]. Parental cells were co-cultured for 24 h prior to addition of antibiotics [7]. The origin of hybrid cells by cell fusion and not horizontal gene transfer was proven by short tandem repeat (STR) analysis, whereby specific sequences on different chromosomes were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, cancer cells can fuse with different cell types, including stromal, epithelial and endothelial cells generating genetically instable hybrids202122. Additionally, it was shown that macrophages or bone marrow-derived cells behave as fusion partners in several types of tumours2324252627.…”
mentioning
confidence: 99%